Learned Ignorance in the Medicine Bow Mountains : a Reflection on Intellectual Prejudice. - Clifford, Craig. (Value Inquiry Book Series, 2008)
This book is an apologia for the rooted intellectual against the disdainful condescension of the cosmopolitan intellectual-an apology in the Socratic sense of the word. It reflects the author's Texas rootedness unapologetically and offers a polemical but thoughtful indictment of the intellectual prejudice against rootedness; but it is ultimately about the universal human struggle with origins.